Security and immutability of open data in healthcare - Guimarães, Tiago André Saraiva (2023)
Clinical data are sensitive data given the origin of the information. Since the implementation of health information systems, some issues such as interoperability, security, and privacy have been strongly questioned. Storing and consulting them raises the same concerns. Given these concerns, any attempt to introduce healthcare information systems must guarantee the security and privacy, integrity, and immutability of patient information. It is in this sense that blockchain technology and the openEHR open data model appear, as they manage to guarantee interoperability between systems, data security and guarantees about queries of each stored data. In order to understand how to increase security and immutability in an implementation of open data models in hospitals, two distinct architectures were developed. In these architectures, several performance tests were carried out. To understand which of them represents more value to a health institution, an analysis of the results was prepared and, consequently, a discussion about them was held to be able to draw the respective conclusions.